The International Encyclopedia of Interpersonal Communication 2015
DOI: 10.1002/9781118540190.wbeic072
|View full text |Cite
|
Sign up to set email alerts
|

Information Manipulation Theory

Abstract: Information manipulation theory (IMT) is a theory of deceptive discourse design, authored by interpersonal communication scholar Steven McCornack. IMT argues that when deceiving others, people play with or “manipulate” relevant information in myriad ways within their discourse. According to IMT, the particular ways in which people manipulate information align with the conversational maxims suggested by philosopher Paul Grice, in his theory of conversational implicature. Although influential in impacting subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(125 citation statements)
references
References 10 publications
2
121
0
2
Order By: Relevance
“…Based on specificity, authentic reviews were rich in nouns and spatial words yet scanty in terms of pronouns. Consistent with prior research (Johnson & Raye, ; McCornack, ; Ott et al, ), authentic reviews appeared more specific than fictitious entries. Fictitious reviews were more exaggerated than authentic ones—a finding consistent with prior studies (DePaulo et al, ; Yoo & Gretzel, ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Based on specificity, authentic reviews were rich in nouns and spatial words yet scanty in terms of pronouns. Consistent with prior research (Johnson & Raye, ; McCornack, ; Ott et al, ), authentic reviews appeared more specific than fictitious entries. Fictitious reviews were more exaggerated than authentic ones—a finding consistent with prior studies (DePaulo et al, ; Yoo & Gretzel, ).…”
Section: Discussionsupporting
confidence: 85%
“…Comprehensibility is the extent to which reviews are easy to understand. Differences in comprehensibility between authentic and fictitious reviews stem from the information manipulation theory (McCornack, ), as well as the self‐presentational perspective (DePaulo et al, ). The information manipulation theory expects authentic and fictitious reviews to differ in quantity and clarity, both of which shape comprehensibility.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…When the distributor gave the receiver less than half the distribution amount and omitted information about the distribution amount, this was categorized deceptive because past research on ultimatum games has found that receivers often view offers of less than half as inequitable and punish their partner as a result (Huck, ; Kim et al, ; Straub & Murnighan, ; Valenzuela & Srivastava, ). Therefore, omitting information about the offer being less than half the distribution amount was advantageous to the distributor and deceptive (McCornack, ). However, previous research has found that deceptive omission is often viewed as less deceptive than lies but more deceptive than truths (Ritov & Baron, ; Spranca, Minsk, & Baron, ; Tenbrunsel & Messick, ; Van Swol et al, ; Van Swol, Malhotra, & Braun, ; for an alternative perspective see Levine, ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies suggest that there are certain factors associated with the elicitation of deception. According to the information manipulation theory, deceptive information often violates the conversational principle of quantity; that is, information may be manipulated simply by altering the amount of information that is presented to mislead listeners. The deceiver most likely creates more information when time is available or efforts at persuasion may be beneficial and tends to increase the quantity of information to appear believable or present additional evidence to support his or her deception .…”
Section: Related Work and Hypothesesmentioning
confidence: 99%